Abordagem CTSA no ensino de ecologia: uma contribuição para a formação de cidadãos críticos - Rosa, Isabela Santos Correia (2014)
Considering the broader goals of education, mainly to provide conditions for the full exercise of citizenship, this dissertation aims to contribute to the formation of critical citizens, through the use of this approach in the STSE Education Ecology. For the development of this research, it was considered necessary to meet teachers’ conceptions of the municipalities where the research was carried out (Lagarto, Salgado e Boquim) before discussing teaching Ecology facing the STSE approach, since the evaluation of teachers about the interrelationships STSE has a direct influence on their teaching methodology (FIRME & AMARAL, 2008). Among the results of this initial investigation, we highlight the fact that the majority of teachers whose main difficulty in inserting STSE themes in teaching Ecology, lack of collateral. In this context, we realized the need to offer the teacher an option to enter the STSE focus on Ecology unit in the third grade of high school in order to contribute to the formation of critical citizens. Was then prepared by the researcher, a teaching sequence on the subject, and this was assessed by both teachers of state schools where the research was carried out, as by professors from top schools, and after the necessary adjustments in the material, this was returned to basic education teachers for use in their teaching. We conclude that the majority of teachers who participated in the survey, presents “plausible” views on all the issues discussed on the interrelationships STSE. However, these concepts do not seem to reflect on the assumptions of an indifferent approach STSE pedagogical practice. It is noticed that there is significant difference between teachers in urban and rural municipalities. It appears that the elaborate instructional sequence is a good teaching strategy and adequately addresses the relationships between Science, Technology, Society and Environment. In his speeches, teachers seek to address controversial issues in lessons of Ecology, considering both interesting and able to attract the attention of students, how to be a recurring theme of evidence NHSE. Teachers highlighted the lack of interest by students of subjects related to the environment, and the need to recover the sense of them critical. In sum, it is expected that the instructional sequence developed, will be used by teachers who participated in the survey and may contribute to the formation of critical citizens with a broader understanding of issues involving Science, Technology, Society and environment. If this occurs, the results of this study may have some effect on the reality of scientific research and science education.